Nuclear Medicine in Southeast Asia: Bridging The Gap in Infrastructure and Workforce Among Indonesia, Malaysia, and Singapore - B. Ayu Adhitya Asys (PT. Global Research Collaboration, 2026)
Health facilities and nuclear medicine physicians are still limited; it is necessary to improve and develop strategies to meet the needs of these facilities and physicians. This study aims to investigate the current state of health facilities and nuclear medicine physicians in three neighboring countries — Indonesia, Malaysia, and Singapore — and to analyze how these countries' future projections will meet the needs of Their Facilities and Nuclear Medicine physicians. This study employs a literature review approach to identify data needs. All data collected are analyzed to obtain the expected results. Based on the data collected, it was found that Health Facilities in Indonesia, Malaysia, and Singapore have different standards for the ratio of facilities and medical personnel, and none of the countries has fully achieved their expectations. In Malaysia, there are 79 Nuclear Medical Physicians, Indonesia has 58, and Singapore has 36. The three countries have different projections for the development of nuclear medicine. Indonesia focuses on reducing the number of Nuclear medical physicians, Malaysia focuses on improving services and equity, and Singapore focuses on developing Nuclear medicine technology.